Public Relations (PR) dan Corporate Social Responsibility (CSR): Memperkuat Fungsi dan Posisi dalam Manajemen Strategis - Abdul Rohman (Program Studi Ilmu Komunikasi, 2010)
Profession and field of Public Relations (PR) in Indonesia are still on communication technician level. PR has not been put on strategic management function. PR roles in Corporate Social Responsibility (CSR) activities are still often be positioned within communication division. PR still does its traditional function as a media agent. PR shall be involved within every stage of CSR program, either research, planning, communicating, or evaluating stage.